Analysis of the properties of siglalon (Vasconcellea stipulata) and its application in bakery products - Asalia A. Cedeño-Zambrano (2025)
The siglalon is considered a fruit of Colombo-Ecuadorian origin. Its geographical distribution in Ecuador is in the provinces of Azuay, Loja, Cañar, and El Oro. According to the taxonomic classification, the genus Vasconcellea comprises twenty-one species. The application of the Vasconcellea stipulata fruit in the field of bread-making stems from the limited knowledge about siglalon and its use in gastronomy, as its consumption is low in mountainous areas and their surroundings. This culinary proposal is the application of siglalon in baking to take advantage of its nutritional properties. The organoleptic characteristics of this fruit are a great contribution to baked goods. In the methodology, three experiments were established in four preparations, of which the pastry cream was the highest-rated product, with 85 % acceptance. The organoleptic properties of the preparations, such as aroma, color, flavor, and texture, were also characterized in Guayaquil. However, the low score in samples (a) and (b) from the panelists is related to the high presence of tannins in the siglalon, due to the cooking technique used. This research shows innovation in bread-making, demonstrating that siglalon can be successfully incorporated into bakery products for its culinary and nutritional value.